Africa’s Food Security under the Shadow of the Russia-Ukraine Conflict (The Strategic Review for Southern Africa, 2022)
The Russian invasion of Ukraine in February 2022 has emerged as an exogenous shock to global food supply chains, which foreshadows worrying impacts on Africa’s food security and nutrition, and threaten to derail national and global efforts to end hunger and poverty and to achieve sustainable development goals on the continent. This article provides an early assessment of the implications of the invasion for Africa’s food supply chains and food security. Two particularly aggravating factors, which explain the current and likely future impact of the invasion on Africa’s food security are discussed: the timing of the invasion and the two parties involved in the conflict. The article underlines four major channels by which the invasion disrupts African food supply chains: energy markets and shipping routes, availability and prices of agricultural production inputs, domestic food price inflation, and trade sanctions and other financial measures. In addition, the article considers the risk of social and political unrest that disruption to food supply chains and spikes in domestic food prices may inflame. Finally, the paper briefly discusses options for short- and long-term responses by African governments and their development partners to mitigate the repercussions of the conflict on food supply chains, boost food and nutrition security, and build resilience of Africa’s food systems.